Program Projek Penguatan Profil Pelajar Pancasila (P5) dalam Pandangan Filsafat Pendidikan John Dewey - Wahyu Trisno Aji; Meti Rosiana (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study aims to analyze the implementation of the Independent Curriculum in the Pancasila Student Profile Strengthening Program (P5) in the perspective of John Dewey's Educational Philosophy. The focus of this study is on the progressive education approach promoted by Dewey, and its relevance to the principles of P5 which aim to form Indonesian students who have Pancasila character. This study uses a qualitative-descriptive-analytics method, with data collection techniques in the form of library studies. Data are taken from various literatures, including books, journals, articles, and online sources. Data analysis techniques involve data reduction, data presentation, and verification to reach conclusions. The results of this study are expected to provide a deeper understanding of the contribution of Dewey's thinking to the development of a curriculum that emphasizes project-based learning and strengthening national values ​​through holistic and participatory education.